THE RELATIONSHIP BETWEEN LUNG FUNCTION, DISEASE SEVERITY, AND MOTIVATION TO QUIT SMOKING AMONG CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) PATIENTS - Resti Yulianti Sutrisno; Destamaya Sholina Wibowo; Thandar Soe @ Sumaiyah Jamaludin (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Smoking cessation is an important management for Chronic Obstructive Pulmonary Disease (COPD), but many patients continue to smoke due to low motivation. Therefore, further studies exploring the motivation to quit smoking are needed. This study examines the relationship between lung function, disease severity, and motivation to quit in COPD patients.Methods: A correlational cross-sectional study was conducted at a pulmonary hospital in Yogyakarta, Indonesia, in February 2024. One hundred adults with COPD who were current smokers were chosen through random sampling. We used the Richmond Test to measure motivation to quit smoking, the COPD Assessment Test (CAT) questionnaire to assess the severity of COPD, and Peak flow meters to assess lung function by measuring peak expiratory flow (PEF). Descriptive statistics were provided to summarise the characteristics of the participants, and Spearman's rank correlation was used to analyse the relationships between the variables.Results: The average age of the participants was 65 years, the length of time they had been smoking was 23 years, and the number of cigarettes smoked each day was 23. Most respondents showed moderate motivation to quit smoking (70%) and had a diagnosis of severe (60%) COPD. There is a significant correlation between peak expiratory flow and the motivation to quit smoking (p = 0.03) and between the severity of the disease and the motivation to quit smoking (p = 0.04).Conclusion: These findings emphasise the importance of communicating PEF assessment results and disease severity to enhance COPD patients' motivation to quit smoking.